Hubungan antara Aktivitas Merokok dengan Penyakit Hipertensi pada Laki-Laki Usia 45 Tahun ke Atas - Sally Yustinawati Suryatna; Asep Suryadin; Sri Kurnia Dewi (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Hypertension is a major cause of heart failure, stroke and kidney failure. Prevalence of hypertension in Indonesia in the urban and rural areas ranged between 17-21%. Smoking is one cause that can affect blood pressure. The aim of this research is to discover the relationship between the smoking activity and hypertension on men aged 45 year-old and older in Klinik Pratama Cinangsih Medika Cianjur. This research is a correlative descriptive. The approach used cross-sectional with total samples were 98 respondents. The sampling technique used was purposive sampling. The instrument used in this study was questionnaire. Data was obtained through questionnaires distribution and interviews, and blood pressure measurement. The data collected was processed by using Chi-square statistical test with degree of significance p value < 0.05. The result showed 74 people (75,5%) smoked and those who suffered hypertension were 75 people (76,5%). From bivariate test result showed there is relationship between number of cigarettes taken and hypertension (p = 0,005), there is relationship between way of smoking and hypertension (p = 0,008), there was no relationship between smoking duration and hypertension (p = 0,059), there is relationship between type of cigarette and hypertension (p = 0,027), and there is relationship between the activity of smoking and hypertension (p = 0,007). Suggestions the researcher can propose concerning this research are to reduce hypertension risk as the effect of smoking, cigarette consuming should be decreased gradually to stop smoking in advance, the result of this research can be served as reference in dealing with patients suffering for hypertension, especially, in Cianjur. Keywords: Smoking activity (number of cigarette, way of smoking, smoking duration, sort of cigarette), Hypertension.